Developing leadership in the Asia Pacific : a focus on the individual - Phillipson, Sivanes; Phillipson, Shane N. (Milton Park, Abingdon, Oxon : Routledge, 2014)
'Developing Leadership in the Asia-Pacific focuses on the design of leadership programs that are able to meet the needs of students, teachers and the wider community. Rather than taking an all-encompassing approach that cover all contexts of leadership development, this book is based on research that guides the leadership teacher in designing a course that takes into account the specific context and needs of individual students, the purpose of the course, and how the course can be evaluated for its effectiveness.Emphasising learner diversity, the book argues that the students specific cultural and educational contexts need to be taken into account when designing leadership programs. Although these courses are often taught outside of the regular curriculum, components of leadership can be found in the regular curriculum. Accordingly, this book helps the leadership teacher to integrate the leadership program with the regular curriculum through the use of guiding questions, quizzes, case studies, dilemmas, and other pedagogical strategies. It links research with practice, scaffolding teachers in understanding the content or issues described in each chapter, assisting them in building a fully defensible leadership program. A number of real life worked examples are also provided throughout each chapter as a practicable framework that can be used in teaching design for everyday units of work. This book is a useful reference for researchers working in leadership as well as an essential tool for teachers developing leadership programs for students in primary, secondary or tertiary contexts.' --
Includes bibliographical references (pages 256-265) and index.
Keywords: Leadership -- Study and teaching -- Asia; Leadership -- Study and teaching -- Pacific Area; Leadership in children -- Asia; Leadership in children -- Pacific Area; Educational leadership